Outcome of Severe Left Ventricle Systolic Dysfunction Patients After Coronary Artery Bypass Grafting: Severe Left Ventricle Systolic Dysfunction After CABG - Moeen, Muhammad; Azam, Hammad; Mahmood, Mohsin (Pakistan Journal of Health Sciences, 2025)
Coronary artery bypass grafting (CABG) has historically been regarded as a high-risk intervention. Objective: To evaluate the short-term outcomes of severe left ventricular (LV) systolic dysfunction in patients after CABG. Methods: This prospective observational cohort study was done at the Department of Cardiac Surgery, Pervaiz Elahi Institute of Cardiology, Bahawalpur, Pakistan, from August 2022 to September 2024. Patients aged 30–75 years, with confirmed coronary artery disease requiring CABG and ejection fraction (EF) ≤30%, were analyzed. Preoperative variables included demographic information, comorbidities, cardiac function parameters and angiographic findings. Postoperative complications and 90-day mortality were noted. Results: In a total of 78 patients, 53 (68%) were male. The mean age was 55.2 ± 9.3 years. The mean baseline EF was 25.4 ± 4.6%. The mean bypass and cross-clamp times were 90.3±16.8 minutes and 51.4 ± 11.6 minutes, respectively. The most common post-surgery complications were arrhythmias, neurological disorders, wound infection, and acute kidney injury, noted in 12 (15.4%), 6 (7.7%), 5 (6.4%), and 3 (3.8%) patients, respectively. At 90 days postoperatively, mortality was reported in 6 (8.7%) patients. Predictors of 90-day mortality included preoperative EF <25% (OR=3.2, 95% CI:1.2–8.5, p=0.014), age ≥65 years (OR=2.8, 95% CI:1.1–7.0, p=0.021), and left main disease (OR=3.6, 95% CI:1.4–9.1, p=0.008). Conclusions: In terms of short-term outcomes, CABG in patients with severe LV systolic dysfunction is associated with significant improvements in functional status and EF. Key predictors of mortality included preoperative EF <25%, advanced age (≥65 years), and left main disease, highlighting the need for careful preoperative risk stratification.